Anmeldelse af Economic Ideas in Political Time: The Rise and Fall of Economic Orders from the Progressive Era to the Global Financial Crisis - Jensen, Carsten (Politica, 2018)
Wesley W. Widmaier, Economic Ideas in Political Time: The Rise and Fall of Economic Orders from the Progressive Era to the Global Financial Crisis. Cambridge University Press, 2016 (anmeldt af Carsten Jensen)